Adverse effects of smoking on patients with ocular inflammation. Issue 7 (1st July 2010) - Galor, Anat; Feuer, William; Kempen, John H; Kaçmaz, R Oktay; Liesegang, Teresa L; Suhler, Eric B; Foster, C Stephen; Jabs, Douglas A; Levy-Clarke, Grace A; Nussenblatt, Robert B; Rosenbaum, James T; Thorne, Jennifer E
Abstract : Background: To evaluate how smoking affects the time to disease quiescence and time to disease recurrence in patients with ocular inflammation. Methods: A retrospective cohort study of patients with ocular inflammation who were followed longitudinally and had smoking information available in the Systemic Immunosuppressive Therapy for Eye Diseases Cohort Study database. Results: Among 2676 patients with active ocular inflammation, smokers were more likely to have bilateral ocular disease and poorer visual acuity on presentation compared with non-smokers and previous smokers. In a multivariate analysis, there was no statistically significant difference in the time to disease quiescence between groups. However, the median time to recurrence of ocular inflammation was statistically significantly longer for non-smokers (9.4 months) and for previous smokers (10.7 months) than for current smokers (7.8 months) (p=0.02). The RR of ocular inflammation recurrence was higher for smokers than for non-smokers (adjusted HR=1.19, 95% CI 1.03 to 1.37) and tended towards significance in previous smokers (adjusted HR=1.11, 95% CI 0.93 to 1.35). Conclusions: Smoking was associated with an increased likelihood of bilateral ocular inflammation and reduced vision upon presentation, and an increased risk of recurrence compared with not smoking. These results suggest that patients with ocular inflammation should be counselled to stop smoking as part of routine management.